History of Afro-Brazilians, Africans, and anti-racist education: the perspective of professors working on teacher training (Educação e Pesquisa, 2022)
This article aims to expose the understanding of higher education professors about how they approach topics related the teaching of African history and culture and the education for the ethnic-racial relations in the curriculum of the teacher-training courses in human sciences in the Center-West region of Brazil. Above all, in relation to the adequacy of the formation itineraries of future teachers of Basic Education, as set forth by Law No. 10.639/2003 and in the National Curriculum Guidelines for the Education of Ethnic-Racial Relations (2004). The objects of the research are the University of Brasília, the University of Goiás, the Federal University of Mato Grosso, the Federal University of Mato Grosso do Sul, and the Federal University of Grande Dourados. Out of the 104 teacher-training courses, 50 have absorbed the them, 48 still do not have specific disciplines on ethnic-racial issues and, in six courses, it was not possible to identify them. The study complements the analysis of the respective disciplines, programs and bibliography. The analysis of the applied questionnaires indicated that restructuring the curricular grids has much more to do with the efforts of professors/researchers in the area as to acknowledge how important theme is than fulfilling legal requirements. Likewise, it was not possible to identify robust institutional involvement beyond the actions developed by the Afro-Brazilian and African Studies Centers (NEABs).